A descriptive survey on the effects of internship of selected UP interior design students in relation to skills and competencies of the interior design profession - Cruz, Marie Annjeannette B. author
This study explored the effects of internship to selected UP interior design students, in relation to skills and competencies required by the interior design profession. The participants of this study included twenty UP interior design students who have accomplished at least 200 hours of internship work within the past 12 months. As an internship is often described as a transition from academic education to professional work, the learning experience of interior design students in their internship was examined using the following factors: students' pre-internship competencies, internship setting, and internship work. This was done by determining the tasks assigned to interior design interns in different design firms, how these tasks tested their pre-internship competencies, and how their internship helped them become more confident with their interior design skills and competencies. The study was a two-phase descriptive survey that used survey questionnaires and in-depth interviews. The participants of the study were selected through purposive sampling based on the set criteria. The results of the study concluded differences on the skills learned by interior design interns in different design firms (i.e. interior design firms, architecture firms, and interior design-furniture firms). Furthermore, it concluded positive effects of internship to the students' self-efficacy or confidence on their capabilities and skills for the interior design practice. This proved effectiveness of a holistic kind of education wherein theory and practice are combined. For further research, a wider scope that includes interior design students from other academic institutions may be considered, and concepts such as professional culture and values may be incorporated.